Locus Of Control Pemoderasi Pengaruh Kecerdasan Intelektual, Emosional, dan Spiritual Pada Keputusan Etis Konsultan Pajak - Pratama, I Made Indra; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2018)
This study aims to examine the influence of intellectual, emotional, and spiritual intelligence on ethical decisions of tax consultants with locus of control as a moderating variable. The research population is all tax consultants who work at tax consultancy office in Bali area. The sample of research is determined by using purposive sampling method, the criterion used is a tax consultant who has at least one certificate brevet. Data analysis technique used in this research is multiple linear regression analysis and moderates regression analysis. The test results prove that intellectual intelligence variables affect the ethical decisions, emotional intelligence affects ethical decisions, spiritual intelligence influences ethical decisions. Locus of control moderate the influence intellectual intelligence, emotional intelligence, and spiritual intelligence on ethical decisions. Keywords: Intellectual intelegence, emotional, spiritual, locus of control